Last updated at May 12, 2021 by Teachoo

Transcript

Example 4 Show that tan-1 1/2 + tan-1 2/11 = tan-1 3/4 Taking L.H.S tan-1 1/2 + tan-1 2/11 = tan-1 (1/2 + 2/11)/(1− 1/2 × 2/11) = tan-1 (1/2 + 2/11)/(1− 1/11) = tan-1 ((1(11) + 2(2))/(2 × 11) )/((1(11) − 1)/11) = tan-1 ((11 + 4)/(2 × 11) )/((11 − 1)/11) = tan-1 (15/(2 × 11) )/(10/11) = tan-1 (15/(2 × 11) × 11/10) = tan-1 3/4 We know that tan-1 x + tan-1 y = tan-1 ((𝒙 + 𝒚 )/(𝟏 −𝒙𝒚)) Replacing x by 1/2 and y by 2/11 = R.H.S. Thus L.H.S = R.H.S Hence proved

Examples

Example 1
Important

Example 2

Example 3 (i) Important

Example 3 (ii)

Example 4 Deleted for CBSE Board 2022 Exams You are here

Example 5 Important Deleted for CBSE Board 2022 Exams

Example 6 Important Deleted for CBSE Board 2022 Exams

Example 7 Deleted for CBSE Board 2022 Exams

Example 8 Deleted for CBSE Board 2022 Exams

Example 9 Important

Example 10 Important Deleted for CBSE Board 2022 Exams

Example 11 Important Deleted for CBSE Board 2022 Exams

Example 12 Important Deleted for CBSE Board 2022 Exams

Example 13 Important Deleted for CBSE Board 2022 Exams

Chapter 2 Class 12 Inverse Trigonometric Functions (Term 1)

Serial order wise

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.